Large T cell clones expressing immune checkpoints increase during multiple myeloma evolution and predict treatment resistance - Botta, Cirino; Perez, Cristina; Larrayoz, Marta; Puig, Noemi; Cedena, Maria-Teresa; Termini, Rosalinda; Goicoechea, Ibai; Rodriguez, Sara; Zabaleta, Aintzane; Lopez, Aitziber; Sarvide, Sarai; Blanco, Laura; et al. (Nature Communications, 2023)
Tumor recognition by T cells is essential for antitumor immunity. A comprehensive characterization of T cell diversity may be key to understanding the success of immunomodulatory drugs and failure of PD-1 blockade in tumors such as multiple myeloma (MM). Here, we use single-cell RNA and T cell receptor sequencing to characterize bone marrow T cells from healthy adults (n = 4) and patients with precursor (n = 8) and full-blown MM (n = 10). Large T cell clones from patients with MM expressed multiple immune checkpoints, suggesting a potentially dysfunctional phenotype. Dual targeting of PD-1 + LAG3 or PD-1 + TIGIT partially restored their function in mice with MM. We identify phenotypic hallmarks of large intratumoral T cell clones, and demonstrate that the CD27− and CD27+ T cell ratio, measured by flow cytometry, may serve as a surrogate of clonal T cell expansions and an independent prognostic factor in 543 patients with MM treated with lenalidomide-based treatment combinations.